Acquisition and consolidation of novel morphology in human neocortex: A neuromagnetic study. (October 2016) - Leminen, Alina; Kimppa, Lilli; Leminen, Miika M.; Lehtonen, Minna; Mäkelä, Jyrki P.; Shtyrov, Yury
Abstract: Research into neurobiological mechanisms of morphosyntactic processing of language has suggested specialised systems for decomposition and storage, which are used flexibly during the processing of complex polymorphemic words (such as those formed through affixation, e.g., boy + s  = noun + plural marker or boy + ish  = noun plus attenuator). However, neural underpinnings of acquisition of novel morphology are still unknown. We implicitly trained our participants with new derivational affixes through a word–picture association task and investigated the neural processes underlying formation of neural memory traces for new affixes. The participants' brain activity was recorded using magnetoencephalography (MEG), as they passively listened to the newly trained and untrained suffixes combined with real word and pseudoword stems. The MEG recording was repeated after a night's sleep using the same stimuli, to test the effects of overnight consolidation. The newly trained suffixes combined with real stems elicited stronger source activity in the left inferior frontal gyrus (LIFG) at ∼50 msec after the suffix onset than untrained suffixes, suggesting memory trace formation for the newly learned suffixes already on the same day. The following day, the suffix learning effect spread to the left superior temporal gyrus (STG) where it was again manifest as a response enhancement, particularly at ∼200–300 msec after the suffix onset, which might reflect an additional effect of overnight consolidation. Overall, the results demonstrate the rapid and dynamic processes of both immediate build-up and longer-term consolidation of neocortical memory traces for novel morphology, taking place after a short period of exposure to novel morphology and involving fronto-temporal perisylvian language circuitry.